Conversos, Accommodation, and the Goan Inquisition: The First Five Decades of the Society of Jesus in India, between Theory and Practice - Blankemeyer, Bradley T. (Archivum historicum Societatis Iesu, 2022)
This article explores the complex connections that the Society of Jesus had with coliversos - as members themselves in the Society, as prospective entrants, and as subjects of the Portuguese Estado da India. It investigates these connections with specific reference to the situation in Goa and Cochin during the first five decades of the Society's presence in India, from the 1540s to the 1580s, and in relation to two important aspects of the missions in India: the Goan Inquisition and Jesuit 'accommodation'. By looking at the origins of Jesuit attitudes to the coliuerso question - both inside and outside the Society - and at Jesuit discussions of Jews who retained their religion in the diaspora as well as those Christian converts from Judaism in India, the article seeks to discern the wide range of opinions in the Society that provided the key elements and limits of missionary 'accommodation' and Jesuit distinctiveness. (English)